Metodika razvitija special'noj vynoslivosti kvalificirovannych lyžnikov-gonšcikov na osnove uceta individual'nych osobennostej fiziceskoj podgotovlennosti i trebovanij sorevnovatel'noj dejatel'nosti - Chromov, V. A.; Golovacev, A. I.; Tarasova, L. V.; Pankov, V. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The paper describes the innovative method for improving the training process of skiers and racers in the preparatory period of sports training. Studies were conducted at a distance of 5000 m, in conditions of rough terrain, at a circular distance of 1000 m. Three methods widely used in the practice of skiing - uniform, variable (continuous) and interval (discontinuous) methods of training - has been studied. It is shown that the use of training loads with variable intensity, in combination with uniform and repeated running, leads to favorable changes in the body and promotes the development of athletes` training. The speed of performance of the training work should be in the range from 70 to 100% of the competitive speed. Developed methods of training of skiers-racers allow you to adjust the intensity of movement on skis and manage the training process, which contributes to the efficiency of building training loads in the preparatory period.